Facial Features and the Effectiveness of Apology - FRANC, Michal (Institutional Knowledge at Singapore Management University, 2014)
Apology is an important tool for the maintenance of positive and cooperative relationships in the workplace. This paper reviews the existing research in the field of apology, and identifies four main components of apology. It uses impression management theory and signaling theory to explain the effect of apology. In addition, it proposes moderating effect of the offender's facial dominance on the effectiveness of apology. Specifically, previous research (e.g., Perrett et al., 1998) found that people with high facial dominance are less trustworthy, which suggests that apology may act as an equalizer between people with high and low facial dominance. Through application of signaling and impression management framework it generates concrete predictions about the apology outcomes. Scenario-based within-subject Study 1 revealed that offers of compensation are the most effective type of apology in workplace context. Offers of compensation are even more effective when used by people with high facial dominance as compared to people with low facial dominance. Our analysis also showed that perceived sincerity of apology is the underlying mechanism that explains these differences. Between-subject Study 2 used behavioral measures of trust restoration. Using PDG paradigm, one hundred forty three participants experienced defection during their ii interaction with dominant versus non dominant partner and offered different types of apologies or no apology. While the results suggested people reacted differently on no apology vs. apology conditions, we did not find any differences between different types of apology, which suggests that there might be difference between our beliefs about how we would react to different apologies (results of Study 1), while we do not make these distinctions in real situations (results of Study 2). Implications of these findings for Impression Management and Signaling theory are discussed. In addition, we proposed practical implications of our findings.